Safety Analysis Using Seven Basic Quality Tools Fishbone Diagram - Agus Wiranto (INFOKUM, 2025)
Workplace hazards have the potential to cause occupational diseases. Occupational diseases are illnesses caused by work and/or the work environment (Presidential Regulation Number 7 of 2019 on Occupational Diseases). The importance of knowledge about occupational diseases is crucial because many people do not realize that the health problems they experience are the result of their work. Occupational diseases can be prevented, but if they are detected too late, they can lead to more serious health problems, which will have a greater impact on the workforce and increase healthcare management costs, ultimately reducing work productivity. The aim of this research is to prevent the occurrence of occupational diseases using the Decision Support System (DSS) method with the Seven Basic Quality Tools Fishbone Diagram, which helps analyze various issues related to the impact of occupational diseases. Moreover, this method has many other functions and benefits, as it identifies the cause-and-effect relationships between the variables (factors) causing the problem (X) and the resulting variables. Several methods were used in this research to gather data and perform appropriate analysis. This approach can assist fieldwork and be used to experience the process of work safety and health directly. The Fishbone Diagram, also known as the Ishikawa diagram or cause-and-effect diagram, is a tool used to identify the root causes of problems. The name comes from Kaoru Ishikawa, a Japanese quality control expert who developed this concept in the 1960s. Organizations across various industries, including manufacturing, healthcare, and services, use the Fishbone Diagram to identify and analyze the factors contributing to specific problems or issues. Teams typically use the diagram to identify all possible causes of a problem or effect. They label these causes based on major contributing factors, such as people, equipment, materials, environment, and methods. Once all the causes are identified and listed, the next step is to analyze the relationships between them to identify the root cause of the issue. This can be done using various techniques, such as the "5 Whys" method, where one repeatedly asks why a problem occurred until the root cause is identified. The results of the research showed that the risk value for occupational diseases, specifically respiratory disorders, before the implementation of the Fishbone Diagram was 12 incidents, and after the implementation, the number of incidents decreased to 4.